Study of Cyclicity and Synthesis of Energy Production to Economic Growth in East Java Province - Eva Violeta; Shenia Endika (East Java Economic Journal, 2020)
Energy use is considered as one of the supporting factors in increasing a country’s economic growth. Sensitive issues in recent periods have involved the issue of energy supply, which has also become one of the main concerns for the economy of a region, such as East Java Province. In recent years, electricity production and distribution shrink in East Java has increased. The problem is believed to be able to affect the economic growth of East Java Province. Based on the built background, this research tries to see the relationship in the short-term and long-term between energy production and economic growth. To answer this question, 3 main analytical methods were used, namely Quantitative Descriptive Analysis, ARDL Bound testing, and Dynamic Ordinary Least Squares (DOLS). This study is also supported by the Granger Causality test to determine the causal relationship between the variables used. The main research results show that there is a significantrelationship between energy production and economic growth. These results indicate that an expansion in energy production is expected to lead to higher growth and a shortage in energy production could hinder the process of economic growth.